2015
DOI: 10.5657/kfas.2015.0529
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Community Structure of Demersal Fish Caught by a Danish Seine Fishery in the Coastal Waters of the Middle and Southern East Sea, Korea

Abstract: We examined the species composition and community structure of demersal fish in the middle and southern coastal waters of the East Sea of Korea by surveying a commercial Danish seine fishery from 2010 to 2013. We considered the waters north of 37°N as middle and those south of 37°N as southern waters. A total of 79 demersal fish species belonging to 18 families were collected. Of these, 59 species (77.6%) inhabited only the East Sea as opposed to the West and South Seas of Korea, and most were resident species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the present study, the total composition and abundance of fish species collected from the sampling sites during the two seasons were similar to those previously reported in the East and South Seas of Korea [34][35][36][37]. In particular, clearly distinct dominant species between the two seas are among the most common characteristics of fisheries resources in Korean coastal waters, as reported in many studies [34,[38][39][40]. The relatively high diversity of fish species in the South Sea (47 and 36 species recorded in May and October, respectively) compared to those in the East Sea (12-16 and 19 species recorded in May and October, respectively) may be related to the unique environmental conditions created by complex interactions caused by the TWC input from the south and nutrient-enriched freshwater from major river systems of Seomjin, Nam, and Nakdong River (Moon et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the total composition and abundance of fish species collected from the sampling sites during the two seasons were similar to those previously reported in the East and South Seas of Korea [34][35][36][37]. In particular, clearly distinct dominant species between the two seas are among the most common characteristics of fisheries resources in Korean coastal waters, as reported in many studies [34,[38][39][40]. The relatively high diversity of fish species in the South Sea (47 and 36 species recorded in May and October, respectively) compared to those in the East Sea (12-16 and 19 species recorded in May and October, respectively) may be related to the unique environmental conditions created by complex interactions caused by the TWC input from the south and nutrient-enriched freshwater from major river systems of Seomjin, Nam, and Nakdong River (Moon et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The relatively high diversity of fish species in the South Sea (47 and 36 species recorded in May and October, respectively) compared to those in the East Sea (12-16 and 19 species recorded in May and October, respectively) may be related to the unique environmental conditions created by complex interactions caused by the TWC input from the south and nutrient-enriched freshwater from major river systems of Seomjin, Nam, and Nakdong River (Moon et al, 2015). Similarly, fish communities in the East Sea are mostly comprised of resident and/or demersal fishes, such as the families Pleuronectidae and Cottidae, suggesting that certain biological characteristics occur only in the eastern coastal waters of the Korean Peninsula rather than in the South Sea [35,39].…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the fish species collected at the Hupo site was mainly resident and benthic temperate fish, such as Glyptocephalus stelleri and Gymnocanthus herzensteini, which is consistent with a previous report on the eastern coast of the Korean peninsula (Choi et al, 2012;Park et al, 2020a). The fish communities on the east coast of the Korean peninsula are characterized by a high proportion of the endemic and resident species (Sohn et al, 2015). In contrast, relatively few species of tropical and subtropical fish taxa, such as Thamnaconus modestus and Sebastes zonatus were found in assemblages collected from the Ulleungdo and Dokdo sites.…”
Section: Effect Of Environmental Factors On Fish Community In the Off...supporting
confidence: 90%
“…The average total composition and abundance of fish species (27 species and 899 individuals) assessed in Hupo coastal waters over four seasons were similar to the ranges previously reported for the eastern coast of the Korean peninsula (17 Pleuronectidae (H. pinetorum, G. stelleri, and P. herzensteini; 55.8% of total abundance) and Cottidae (G. herzensteini and G. intermedius; 26.2% of total abundance), which were mainly resident demersal fish. Despite differences in sampling efforts and equipment, several studies have also shown that the dominant fish species in the coastal waters of the East Sea are mainly resident benthic and benthopelagic species (Lee 2011;Choi et al 2012;Kang et al 2014;Sohn et al 2015). In particular, the three species H. pinetorum, G. stelleri, and G. herzensteini are commonly distributed along the eastern coast of the Korean peninsula (Ryu et al 2005;Hong et al 2008;Lee 2011;Choi et al 2012).…”
Section: Community Characteristics Of Fish Assemblagesmentioning
confidence: 99%
“…Similarly, off the eastern coast of Korea, some species such as G. stelleri and C. pinetorum move from nearshore waters into a deeper shelf and/or more offshore waters as they grow (Lee 2011). In general, seasonal fluctuations in fish composition and abundance are attributable to sequential patterns of migration and emigration by several species, and may be a feature of fish communities off the eastern coast of the Korean peninsula (Lee 2011;Choi et al 2012;Kang et al 2014;Sohn et al 2014Sohn et al , 2015.…”
Section: Community Characteristics Of Fish Assemblagesmentioning
confidence: 99%